Basic life support training for people with disabilities. A scoping review - Carlos Berlanga-Macías; Roberto Barcala-Furelos; Nerea Méndez-Seijo; Lucía Peixoto-Pino; Santiago Martínez-Isasi (Resuscitation Plus, 2023)
Background: The integration of populations with various types of disabilities into basic life support (BLS) training programs could contribute to a potential increase in trained laypersons with BLS knowledge and, consequently, in survival rates. The objective of this study was to analyze the distinct educational methods which exist today on BLS for people with some type of specific disability, and to evaluate their impact on the quality of BLS maneuvers. Methods: A scoping review in which the different training strategies in BLS for people with distinctive disabilities were analyzed was carried out. Previous studies were sought and researched in MEDLINE, EMBASE, and the Cochrane Library from the beginning up to 4 August 2023. Results: A total of 14 studies were thoroughly analyzed. The BLS training strategies for people with disabilities were classified according to the following criteria: objective (training, content validation or analysis of learning barriers), target population (visual, hearing, physical disabilities or Down syndrome), training resources (training with/without adaptation), contents (BLS and use of the automated external defibrillator) and evaluation instrument (i.e., the simulation test and knowledge questionnaire). The variety of BLS training programs for such population is limited. Likewise, people with different disabilities are able to effectively learn BLS maneuvers, although with mixed results, mainly in those regarding the CPR quality. Conclusion: People with visual, hearing disabilities or Down syndrome are able to effectively learn BLS maneuvers.